اثر شبكات التواصل الاجتماعي في تفعيل الوعي السياسي للكوادر الحزبية الكوردية - احمد, ا.م.د. فواد علي (Sulaimani Journal for Humanities, 2023)
The impact of social networks in activating the political awareness of Kurdish party cadres The research tagged (The impact of social networks in activating the political awareness of the Kurdish party cadres), consists of two parts, theoretical and field, and the first part of the research includes the introduction and methodology of the research, which consists of: the research problem, its importance, its objectives, its community, its sample, the professional characteristics of the respondents, its methodology, fields, tools, methods, apparent honesty and stability And the instructions of the scale, while the research concepts are a brief explanation of the existing basic concepts and explain them in a brief explanation. As for the second part, it dealt with a presentation of the results of the research questionnaire and its analysis, and the impact of social networks in activating their political awareness, then it dealt with an explanation of the results of that field study supported by tables and statistics, and then the researcher presented the research conclusions, recommendations and proposals, and a list of references and sources and a summary of the research in English. This study is classified within the descriptive research, and relied on the survey method, and the researcher adopted a three-point Likert scale to build the scale, and the final paragraphs included (15) fifteen paragraphs after presenting it to a group of experts from media sciences to see the extent of its suitability for the validity of the scale, and the researcher tested the research sample in a method The systematic non-random sample (intentional) on the respondents from the partisan cadres of (the Patriotic Union of Kurdistan and the Justice Group in Kurdistan / Iraq) and their number is (101) respondents as the research sample.
Keywords: social networks; activation; political awareness; party cadres